Software agents and contracts - Andrade, Francisco Carneiro Pacheco (2008)
In the current economical context, characterized by the existence of a global society, the access to information is crucial for any economical and social development; yet, important technological challenges still remain. The representation, maintenance, and querying of information is a central part of this problem. How can we obtain the adequate information at the adequate time? How can we supply the correct items for the correct people at the correct time? How and where can we get the relevant information for a good decision-making? The organizations focus their competences in strategical areas and have recourse to external supplies, cooperating with sporadic partners, with the objective of reducing costs, risks, and technological faults or maximizing benefits and business opportunities. One of the most radical and spectacular changes is the information dematerialization, the procedure automation, the recourse to decision support systems or intelligent systems, and to new forms of celebrating contracts (e.g., is it possible to practice commercial acts and celebrate deals using autonomous and pro-active computational agents?). The virtual organizations face new challenges and there must be a search for new answers to old questions. The negotiation processes through electronic means and the e-commerce platforms may set new forms of contracts, with engagements and negotiations among virtual entities.